Pericentric Inversion in Chromosome 10 in a Girl, Inherited from a Phenotypically Normal Mother: Case Report and Literature Review - Sotoudeh Anvari, Maryam; Taghvaei, Behrang; Vasei, Mohammad (International Journal of Negative Results, 2017)
Pericentric inversions in chromosome 10 are regarded as both common and rare conditions, based on breakage and rearrangement within each specific segment. We present phenotypic and cytogenetic characterizations of a rare recombinant chromosome 10, namely inv(10)(p11q26), in a 13-month-old flabby girl associated with a maternal pericentric inversion. A review of the literature on the different aspects of this condition is also provided.
Keywords: Pericentric Inversion; Chromosome 10; Abnormal phenotype